تأثير التفاعل الاجتماعي للطلاب مع المعلمين وطريقة التعلم على نتائج تعلم اللغة العربية للصف العاشر في كلية المعلمين الإسلامية الججر الإسلامي سوراكرتا - Aji, Nur Utomo Bayu; Hafidah, Hafidah (El-Hayah, 2022)
This study aims to determine the effect of: 1) The social interaction of students with teachers on students' Arabic learning outcomes, 2) The jigsaw learning model on students' Arabic learning outcomes 3) Students' social interactions with teachers and the jigsaw learning model on the students' Arabic learning outcomes. This research uses correlational quantitative type. The instrument used in this research is a questionnaire and the test instrument. The results showed that there was no effect between: 1) the social interaction of students and teachers on Arabic learning outcomes with t count 1.113 not less 2.060 t, meaning that there was no effect. 2) The jigsaw learning model on Arabic learning outcomes with t count 1.311 not less 2.060 t table meaning that there was no effect. 3) Students' social interaction with teachers and jigsaw learning model on Arabic learning outcomes with F count 1.312 not less 3.39 F table meaning that there was no effect.